FAKTOR YANG BERPENGARUH TERHADAP STRUKTUR MODAL DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Agustin Nuraini; Endang Masitoh W; Yuli Chomsatu (Accounting Global Journal, 2020)
Capital structure is one of the complex financial decisions because it is related to other financial decision variables. The purpose of this study is to analyze the factors that influence the capital structure with profitability as a moderating variable. The population in this study is the registered food and beverage sub-sector companies. on the Indonesia Stock Exchange in 2014-2018. The sampling technique in this study used a purposive sampling method and obtained a sample of 12 companies. The data analysis method uses the classical assumption test and multiple linear regression analysis using SPSS 20, with the results of data analysis showing company growth and business risk has no effect on capital structure, while liquidity has a negative and significant effect on capital structure, asset structure has a positive and significant effect on structure capital while profitability has a negative effect on capital structure. Profitability is not able to moderate the effect of company growth, business risk and asset structure on capital structure but profitability is able to moderate the effect of liquidity on capital structure.